Cross-category indulgence: Why do some premium brands grow during recession?. Issue 5 (September 2016) - Mark, Tanya; Southam, Colette; Bulla, Jan; Meza, Sergio
Abstract Reports about luxury categories and premium brands growing during recession are multiple. This marketplace behavior, however, is counterintuitive to what traditional economics would predict. The authors propose and test a theory to explain why demand for premium brands may grow despite a contraction in the economy. They define cross-category indulgence as the strategy of moving across categories (in contrast to moving within category) to satisfy the desire to indulge while dealing with budgetary constraints. The authors test empirically for cross-category indulgence using a unique dataset that compares dining in with dining out. They find support for cross-category indulgence and rule out other possible explanations for the increase in demand for a premium brand. The authors discuss that premium brand managers that understand this marketplace behavior and create opportunities for their brand to be the leader in their category may alleviate a decrease in demand for their brand during tough economic times.